Authority as a defining feature and main content of the State essence. (Journal of actual problems of jurisprudence, 2016)
This article highlights the nature, multidimensional character and various types of authority, as well as types of modern authority. Genesis of authority has been evaluated in terms of contemporary Constitution law. The legal evaluation of authority relations in contemporary democratic society and development tendencies have been presented. Specific features of public (political) authority of the Republic of Kazakhstan have been analyzed.
Keywords: state; power; law; society